Reversible discrete event formulation and optimistic parallel execution of vehicular traffic models. (22nd September 2009) - Yoginath, Srikanth B.; Perumalla, Kalyan S.
Vehicular traffic simulations are useful in applications such as emergency planning and traffic management, for rapid response and resilience. Here, a parallel traffic simulation approach is presented that reduces the time for simulating emergency vehicular traffic scenarios. We use a reverse computation-based optimistic execution approach to parallel execution of microscopic, vehicular-level models of traffic. The unique aspects of this effort are: exploration of optimistic simulation of vehicular traffic; addressing the related reverse computation challenges; achieving absolute, as opposed to self-relative, speedup. The design, development and performance study of the parallel simulation system is presented, demonstrating excellent sequential and parallel performance. A speed up of nearly 20 on 32 processors is observed on a vehicular network of 65, 000 intersections and 13 million vehicles.